Consecutive Exotropia: Risk Factor Analysis and Management Outcomes. Issue 2 (March 2014) - Ceylan, Osman Melih; Gokce, Gokcen; Mutlu, Fatih Mehmet; Uludag, Huseyin Avni; Turk, Adem; Altinsoy, Halil Ibrahim
Purpose: To report the frequency of risk factors and outcomes of consecutive exotropia (XT) following bimedial rectus recession (BMR) for the treatment of childhood esotropia (ET). Methods: Ninety-eight patients with ET, who underwent only BMR between 1996 and 2007, were included in this study. Predictors of the development of consecutive XT and treatment outcomes were compared between groups (group 1, cases with consecutive XT; group 2, cases without consecutive XT). Results: Mean follow-up time after BMR surgery was 7.23 ± 3.62 years. There was no significant difference between the groups in terms of age, preoperative angle of near deviation, follow-up time, or refraction for both eyes (p>0.05 for all). The differences regarding preoperative angle of distance deviation (p = 0.009), presence of inferior oblique overaction (p = 0.023), amount of BMR (p = 0.028), and postoperative adduction limitation (p<0.0001) between the groups were statistically significant. However, only preoperative angle of distance deviation and presence of postoperative adduction limitation were independent risk factors for the development of consecutive XT (p = 0.043, p = 0.007, respectively). Conclusions: Postoperative adduction limitation should alert physicians to the increased risk of developing consecutive XT in the long-term follow-up after BMR for the treatment of childhood ET.